Treatment of organophosphate intoxication using cholinesterase reactivators: facts and fiction - Bajgar, Jiri; Fusek, Josef; Kuca, Kamil; Bartosova, Lucie; Jun, Daniel (Mini reviews in medicinal chemistry, 2007)
Basic part of the current standard treatment of organophosphate (OP) agent poisoning is administration of cholinesterase reactivators. It includes different types of oximes with a similar basic structure differing by the number of pyridinium rings and by the position of the oxime group in the pyridinium ring. Oximes hydrolytically cleave the organophosphates from acetylcholinesterase (AChE), restoring enzymatic function. This reactivation of AChE is dependent on the type of the agent and, on the reactivator used. From the common oximes, mono- and bisquaternary pyridinium oximes are more or less frequently used in clinical practice such as pralidoxime, obidoxime, trimedoxime, and HI-6. Though there are data on a good therapeutic effects of reactivators, some attempts to undermine the role of reactivators as effective antidotes against OP poisoning have been made. Some arguments on the necessity of their administration following OP poisoning are discussed with the aim to resolve the question on their effective use, possible repeated administration in the treatment of OP poisoning, their peripheral and central effects including questions on their penetration through the blood brain barrier as well as a possibility to achieve their effective concentration for AChE reactivation in the brain. Reactivation of cholinesterases in the peripheral and central nervous system is described and it is underlined its importance for the survival or death of the organism poisoned with OP. An universality of oximes able to reactivate AChE inhibited by all OP is questioned and trends (molecular modelling using neural network, structure-activity relationship, combination of reactivation and anticholinergic properties in one molecule) for future research are characterized.
Keywords: molekulární struktura; reaktivátory cholinesterasy; Cholinesterase Reactivators; Molecular Structure; Antidotes; cholinesterasy; organothiofosforové sloučeniny; antidota; lidé; Humans; Organothiophosphorus Compounds; Cholinesterases